1989
DOI: 10.1029/jd094id08p11106
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric depositional characteristics of beryllium 7 and lead 210 along the southeastern Virginia coast

Abstract: Atmospheric depositional fluxes of 7Be and 210Pb were measured simultaneously in wet‐only and bulk deposition over a 29‐month period (October 1982 through February 1985) in Norfolk, Virginia (36°53′N, 76°18′W). Total precipitation accumulation during 1983 and 1984 was 134 and 129 cm, respectively, slightly above the normal yearly accumulation. The volume‐weighted average concentrations of 7Be in bulk deposition for 1983 and 1984 were 90 and 100 dpm/L, while those for 210Pb were 5.9 and 6.6 dpm/L, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
72
3
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(86 citation statements)
references
References 75 publications
10
72
3
1
Order By: Relevance
“…Temporal variations of atmospheric influxes at the Goodwin Creek site for the two radionuclides were further examined (table 2) and consistent with long-term measurements from other sites (Todd et al 1989;Wilson et al 2005). At Goodwin Creek, the atmospheric influxes of Moreover, long events or events that are preceded by multiple, other storms may experience washout of the radionuclides before the end of the event (Turekian et al 1983).…”
Section: Resultsmentioning
confidence: 99%
“…Temporal variations of atmospheric influxes at the Goodwin Creek site for the two radionuclides were further examined (table 2) and consistent with long-term measurements from other sites (Todd et al 1989;Wilson et al 2005). At Goodwin Creek, the atmospheric influxes of Moreover, long events or events that are preceded by multiple, other storms may experience washout of the radionuclides before the end of the event (Turekian et al 1983).…”
Section: Resultsmentioning
confidence: 99%
“…We simply average over whatever period the observations cover and compare them with the modelled 5-yr mean fluxes. There are 7 Be observations from 37 stations (Baskaran et al, 1993;Bleichrodt, 1978;Brown et al, 1988;Crecelius, 1981;Hasebe et al, 1981;Heikkilä et al, 2008a;Hirose et al, 2004;Huh et al, 2006;Igarashi et al, 1998;Knies, 1994;McNeary and Baskaran, 2003;Olsen et al, 1985;Todd et al, 1989;Turekian et al, 1983;Uematsu et al, 1994;Young and Silker, 1980), 210 Pb from 71 stations (Baskaran et al, 1993;Graustein and Turekian, 1986;Huh et al, 2006;Hirose et al, 2004;McNeary and Baskaran, 2003;Nijampurkar and Clausen, 1990;Todd et al, 1989;Turekian et al, 1977Turekian et al, , 1983 and 10 Be from 21 stations (Chengde et al, 1992;Graham et al, 2003;Heikkilä et al, 2008a;Monaghan et al, 1986;Somayulu et al, 1984). The modelled 5-yr mean deposition fluxes of 7 Be, 10 Be and 210 Pb are shown in Figures 4, 5 and 6, together with the location and measured flux of the observations.…”
Section: Deposition Fluxesmentioning
confidence: 99%
“…However, the fluxes of 210 Pb in Xiamen were two-to threefold higher than some mid-latitude areas, such as Odawa Bay, Izmir and Huelva (Tateda et al, 2008;Lozano et al, 2011;Uğur et al, 2011). In addition, they were close to some midNorthern regions, i.e., Galveston, Tsuyazaki, Norfolk and Stillpond (Todd et al, 1989;Baskaran et al, 1993;Kim et al, 2000a;Tateda et al, 2008) although higher values were also observed at many mid-latitudes. Similar scenario also happened to 210 Po.…”
mentioning
confidence: 99%